menu
QAmmunity.org
Login
Register
My account
Edit my Profile
Private messages
My favorites
Register
Ask a Question
Questions
Unanswered
Tags
Categories
Ask a Question
Which of the following equations is equivalent to 3(2p + 4) - (3p - 4) = 43? A. 2p + 16 = 43 B. 3p + 16 = 43 C. 2p + 8 = 43 D. 3p + 8 = 43
asked
Jun 7, 2023
96.5k
views
6
votes
Which of the following equations is equivalent to 3(2p + 4) - (3p - 4) = 43?
A. 2p + 16 = 43
B. 3p + 16 = 43
C. 2p + 8 = 43
D. 3p + 8 = 43
Mathematics
college
Vikrantnegi
asked
by
Vikrantnegi
5.3k
points
answer
comment
share this
share
0 Comments
Please
log in
or
register
to add a comment.
Please
log in
or
register
to answer this question.
1
Answer
7
votes
Answer: (use distributive property then add the like terms)
3(2p + 4) - (3p - 4) = 43
6p + 12 - 3p - 4 = 43
3p - 8 = 43
HugoRune
answered
Jun 12, 2023
by
HugoRune
5.0k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
Ask a Question
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.
5.8m
questions
7.5m
answers
Other Questions
Aliyah has $24 to spend on seven pencils. After buying them she had $10. How much did each pencil cost?
Evaluate a + b when a = –16.2 and b = –11.4 A. –27.6 B. –4.8 C. 4.8 D. 27.6
What is the value of x? (-4) - x = 5
Find the quotient of 3,078 ÷ 27. A) 104 B) 109 C) 114 D) 119
Can someone help me with 5??? ASAP?
Twitter
WhatsApp
Facebook
Reddit
LinkedIn
Email
Link Copied!
Copy
Search QAmmunity.org